The Correlation between University Students’ Vocabulary Learning Strategies and The Vocabulary Mastery Level: The Correlation between The Students' Vocabulary Learning Strategies and Vocabulary Mastery Level - Emelia Agustianti; Syofia Delfi; Dahnilsyah Dahnilsyah (J-SHMIC : Journal of English for Academic, 2021)
This research was intended to find the correlation between the students’ vocabulary learning strategies and the vocabulary mastery level. The research design of this study was a quantitative research and the study population was the second year students of English study program FKIP Universitas Riau. 41 participants were selected from the second year students of English Study Program FKIP Universitas Riau using the cluster random sampling technique. The instruments of this study were vocabulary learning strategy questionnaire and vocabulary level test. The data showed that 53.7% of students was used the vocabulary learning strategy in learning new vocabularies and 31.7% students were high vocabulary level. Moreover, the result of the study indicated that there was a negative correlation between two variables. The value of correlation coefficient was 0.813. It was on scale 0.00 – 1.00. It meant that the correlation between the students’ vocabulary learning strategies and the vocabulary mastery level of the second year students were categorized as high correlation. This research would assist students to understand the correlation between used the strategy in learning new vocabularies in order to increase the level of vocabulary mastery.